Utility of dual‐energy computed tomography in the association of COVID‐19 pneumonia severity. Issue 1 (20th December 2022) - Michishita, Takahiro; Saji, Ryo; Miyazaki, Hiroshi; Mishima, Sena; Shimada, Kosuke; Minami, Sakura; Okano, Hiromu; Suzuki, Naoya; Otsuka, Tsuyoshi; Abe, Takeru; Takeuchi, Ichiro; Furuya, Ryosuke
Abstract : Aim: Coronavirus disease 2019 pneumonia differs from ordinary pneumonia in that it is associated with lesions that reduce pulmonary perfusion. Dual‐energy computed tomography is well suited to elucidate the etiology of coronavirus disease 2019 pneumonia, because it highlights changes in organ blood flow. In this study, we investigated whether dual‐energy computed tomography could be used to determine the severity of coronavirus disease 2019 pneumonia. Methods: Patients who were diagnosed with coronavirus disease 2019 pneumonia, admitted to our hospital, and underwent dual‐energy computed tomography were included in this study. Dual‐energy computed tomography findings, plane computed tomography findings, disease severity, laboratory data, and clinical features were compared between two groups: a critical group (18 patients) and a non‐critical group (30 patients). Results: The dual‐energy computed tomography results indicated that the percentage of flow loss was significantly higher in the critical group compared with the non‐critical group ( P < 0.001). Additionally, our data demonstrated that thrombotic risk was associated with differences in clinical characteristics ( P = 0.018). Receiver operating characteristic analysis revealed that the percentage of flow loss, evaluated using dual‐energy computed tomography, could predict severity in the critical group with 100% sensitivity and 77% specificity. However, there were no significant differences in the receiver operating characteristic values for dual‐energy computed tomography and plane computed tomography. Conclusion: Dual‐energy computed tomography can be used to associate the severity of coronavirus disease 2019 pneumonia with high accuracy. Further studies are needed to draw definitive conclusions. Abstract : In this study, we investigated whether dual‐energy computed tomography (DECT) could be used to determine the severity of coronavirus disease 2019 (COVID‐19) pneumonia. DECT can be used to associate the severity of COVID‐19 pneumonia with high accuracy. Further studies are needed to draw definitive conclusions.